Synergic Antitumor Effect of Photodynamic Therapy and Chemotherapy Mediated by Nano Drug Delivery Systems - Mozhgan Aghajanzadeh; Mostafa Zamani; Fereshteh Rajabi Kouchi; Josh Eixenberger; Dorsa Shirini; David Estrada; Farhad Shirini (MDPI AG, 2022)
This review provides a summary of recent progress in the development of different nano-platforms for the efficient synergistic effect between photodynamic therapy and chemotherapy. In particular, this review focuses on various methods in which photosensitizers and chemotherapeutic agents are co-delivered to the targeted tumor site. In many cases, the photosensitizers act as drug carriers, but this review, also covers different types of appropriate nanocarriers that aid in the delivery of photosensitizers to the tumor site. These nanocarriers include transition metal, silica and graphene-based materials, liposomes, dendrimers, polymers, metal-organic frameworks, nano emulsions, and biologically derived nanocarriers. Many studies have demonstrated various benefits from using these nanocarriers including enhanced water solubility, stability, longer circulation times, and higher accumulation of therapeutic agents/photosensitizers at tumor sites. This review also describes novel approaches from different research groups that utilize various targeting strategies to increase treatment efficacy through simultaneous photodynamic therapy and chemotherapy.